A comparison allocation of labor qualification on real, plan, and regulation calculation using resource-leveling method - Servanty, Izmanaya Avril; Putra, I Nyoman Dita Pahang; Soetanto, Robby (Jurnal Sistem dan Manajemen Industri, 2025)
Labor is a crucial resource in industrial construction projects. A common issue is the uneven number of laborers who are overallocated. This study uses the resource-leveling method to compare and determine the optimal number of labor and project duration based on plan, real, and regulation conditions. In this study, the data required in real conditions is obtained from daily report data. In planned conditions, data is obtained from the scheduled manpower made by the contractor, while in conditions based on regulations, the calculation of the number of laborers uses the coefficient values listed in the Regulation of the Minister of Public Works and Public Housing No. 1 of 2022. This research is measured through disparity values, which show an imbalance in the allocation of labor caused by the uneven allocation of labor based on its workload. The results showed a significant difference in the number and distribution of labor. Regulation conditions resulted in higher labor numbers due to detailed calculations on each type of work and labor qualifications. The highest disparity occurs in workers, with a value of 0.93 in the plan condition and -0.51 in the regulation condition. The resource leveling helped balance labor allocation but increased project duration from 98 to 112 working days. These findings provide practical insights for project managers to optimize worker planning and distribution, improve efficiency, and reduce overallocated risks.